Analysis of Electronic Agreements Made by Minors in Ecommerce Transactions in The Perspective of Indonesian Positive Law - Toumahu, Abdul Cholik; Anggraini, Reni (Jurnal Penegakan Hukum dan Keadilan, 2024)
Validity agreements entered into by minors in e-commerce transactions from an Indonesian legal perspective. The current development of technology as we know it is increasingly rapid and pampers all its fans, in this case in digital business activities commonly known as E-commerce. Activities that can be carried out using an internet computer network make it easy for anyone who can do it, including children who are not yet legally capable. This research will discuss the validity of agreements made by children who are not yet able to carry out electronic transactions, whether they are considered valid or not, and the legal consequences for children who are not yet able to carry out e-commerce transactions. The purpose of this research is to find out whether minors agreeing can be considered valid in e-commerce transactions. The method used in this research is a literature review that examines and analyzes library materials using a statutory and conceptual approach. The results of this research will show us that the validity of agreements made by children who are not yet legally competent in e-commerce transactions can be considered valid as long as the agreement does not cause harm to the parties.